Computer-aided approaches reveal trihydroxychroman and pyrazolone derivatives as potential inhibitors of SARS-CoV-2 virus main protease - Atatreh Noor; Hasan Shaima; Ali Bassam R.; Ghattas Mohammad A. (Acta Pharmaceutica)
COVID-19 was declared a pandemic by the World Health Organization (WHO) in March 2020. The disease is caused by severe acute respiratory syndrome coronavirus 2 (SARSCoV-2). The aim of this study is to target the SARS-CoV-2 virus main protease (Mpro) via structure-based virtual screening. Consequently, > 580,000 ligands were processed via several filtration and docking steps, then the top 21 compounds were analysed extensively via MM-GBSA scoring and molecular dynamic simulations. Interestingly, the top compounds showed favorable binding energies and binding patterns to the protease enzyme, forming interactions with several key residues. Trihydroxychroman and pyrazolone derivatives, SN02 and SN18 ligands, exhibited very promising binding modes along with the best MM-GBSA scoring of –40.9 and –41.2 kcal mol−1, resp. MD simulations of 300 ns for the ligand-protein complexes of SN02 and SN18 affirmed the previously attained results of the potential inhibition activity of these two ligands. These potential inhibitors can be the starting point for further studies to pave way for the discovery of new antiviral drugs for SARS-CoV-2.